A qualitative study of factors resulting in care delays for adults with meningitis in Zambia. (2nd June 2022) - Elafros, Melissa A; Bwalya, Chiti; Muchanga, Godfrey; Mwale, Mwangala; Namukanga, Nachizya; Birbeck, Gretchen L; Chomba, Mashina; Mugala-Mulenga, Anchindika; Kvalsund, Michelle P; Sikazwe, Izukanji; Saylor, Deanna R; Winch, Peter J
Abstract: Background: Meningitis causes significant mortality in regions with high comorbid HIV and TB. Improved outcomes are hindered by limited understanding of factors that delay adequate care. Methods: In-depth interviews of patients admitted to the University Teaching Hospital with suspected meningitis, their caregivers, doctors and nurses were conducted. Patient/caregiver interviews explored meningitis understanding, treatment prior to admission and experiences since admission. Provider interviews addressed current and prior experiences with meningitis patients and hospital barriers to care. A conceptual framework based on the Three Delays Model identified factors that delayed care. Results: Twenty-six patient/caregiver, eight doctor and eight nurse interviews occurred. Four delays were identified: in-home care; transportation to a health facility; clinic/first-level hospital care; and third-level hospital. Overcrowding and costly diagnostic testing delayed outpatient care; 23% of patients began with treatment inside the home due to prior negative experiences with biomedical care. Admission occurred after multiple clinic visits, where subsequent delays occurred during testing and treatment. Conclusions: Delays in care from home to hospital impair quality meningitis care in Zambia. Interventions to improve outcomes must address patient, community and health systems factors. Patient/caregiver education regarding signs of meningitis and indications for care-seeking are warranted to reduce treatment delays.